Mixed forest plantation with native and exotic species in a degraded area - Ferreira, Wendy Carniello; Corrêa, Robson Schaff; Freitas, Danival Vieira de; Botelho, Soraya Alvarenga (Revista Ecologia e Nutrição Florestal - ENFLO, 2024)
Reforestation is the main way to recover degraded areas, and the use of a wide variety of species can assist in the recovery process, both in terms of the process itself as cost minimization. The objective of this work was to evaluate the development of a mixed reforestation with native and exotic species in a degraded area by soil compaction. The planting was carried out where there was an unpaved airstrip at Itutinga town, MG. The evaluation of tree species was carried out using five plots of 1,250 m² (25 m x 50 m), systematically distributed. The mechanical resistance of the soil to penetration was determined using an impact penetrometer to a depth of 60 cm. To evaluate the influence of soil mechanical resistance to penetration on tree growth, the Pearson r correlation index was calculated. In the inventory, 534 tree individuals with CAP equal to or greater than 5 cm, belonging to 41 species, were measured and identified in the study area. Most of the inventoried individuals come from species used in planting and most of the species with the highest importance values belong to the ecological group of pioneers. The predominance of trees that are attractive to the fauna and native to the region indicate that the forest succession will occur satisfactorily. The soil resistance to penetration negatively influenced the basal area, that is, the greater the soil compaction in this layer, the lower the occupation of the stand.